RapidLoc 기기를 이용한 반월상 연골판 봉합술 후 조기 재활 프로그램 적용의 임상결과 - 송영준(Young-Joon Song); 하철원(Chul-Won Ha) (The journal of the Korean Orthopaedic Association, 2009)
목 적: RapidLoc 기기를 이용한 반월상 연골판 봉합술 후 조기 재활 프로그램 적용시의 임상결과를 평가하고 이 기기와 관련된 합병증 발생 유무를 알아보고자 하였다. 대상 및 방법: 본원에서 한명의 술자에 의해 RapidLoc 기기를 이용한 반월상 연골판 봉합술 후 조기 재활 프로그램을 적용받은 32명의 환자를 1년 이상 추시하여 그 임상결과를 후향적으로 분석하였다. 환자의 증상과 이학적 검사, International Knee Documentation Committee (IKDC) activity score, Lysholm score를 통해 임상결과를 평가하였고, Barrett의 기준에 의해 관절연의 압통, 관절내 부종, McMurray 검사상 모두 음성 소견을 보이는 경우를 봉합된 반월상 연골판이 치유된 것으로 판단하였다. 결 과: 최종 추시상 IKDC activity score는 술전 1.75점에서 술후 3.38점으로, Lysholm score는 술전 48.7점에서 술후 91.8점으로 호전되었다. 본 연구의 기준에 의해 치유성공이 30예로 임상적 치유율은 93.7%였다. 봉합 실패로 분류된 2예는 관절연의 압통과 운동 후의 간헐적인 부종을 보여 치유 실패로 간주하였다. 전례에서 추시 중 RapidLoc 기기에 의한 특이 합병증을 의심할만한 소견은 없었다. 결 론: RapidLoc 기기를 이용한 반월상 연골판 봉합술 후 조기 재활 프로그램을 적용한 경우에도 우수한 임상결과를 보였으며 안전하고 우수한 봉합수기로 사료된다. Purpose: The purpose of this study was to evaluate the clinical results of the accelerated rehabilitation program after performing meniscal repair using the RapidLoc device, and we wanted to investigate the incidence of complications related to using the RapidLoc device together with the accelerated rehabilitation program. Materials and Methods: We performed a retrospective review of a consecutive series of meniscal repairs that were done by single surgeon with using the RapidLoc meniscal repair device. An accelerated postoperative rehabilitation program followed, and this was independent of whether anterior cruciate ligament (ACL) surgery was also performed. The Lysholm and IKDC (International Knee Documentation Committee) activity scores, the clinical examination findings and the adverse events were recorded for all the patients. In addition, using Barrett's criteria, a repaired meniscus was considered healed if there was no joint line tenderness, effusion or a negative McMurray's test at the latest follow-up. Results: At follow-up, the mean IKDC activity score was 3.38 (1.75 preoperatively), the Lysholm score was 91.8 (48.7 preoperatively). Clinical success occurred for 30 repairs (93.7%) at the time of the last follow-up. Two patient had tenderness on joint line palpation and intermittent effusion, so theses repair were considered failure according to our criteria. There was no specific complication related to the RapidLoc device. Conclusion: Our results show that accelerated rehabilitation program after arthroscopic meniscal repair with using the RapidLoc device provided a high rate of clinical meniscus healing and this appeared to be safe and effective. KCI Citation Count: 0